2011
DOI: 10.1097/ccm.0b013e318206b3ca
|View full text |Cite
|
Sign up to set email alerts
|

Soluble form of the receptor for advanced glycation end products is a marker of acute lung injury but not of severe sepsis in critically ill patients*

Abstract: sRAGE levels were elevated during acute lung injury/acute respiratory distress syndrome, regardless of the presence or absence of severe sepsis. The plasma level of sRAGE was correlated with clinical and radiographic severity in acute respiratory distress syndrome patients and decreased over time, suggesting resolution of the injury to the alveolar epithelium. Further study is warranted to test the clinical utility of this biomarker in managing such patients and to better understand its relationship with lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 39 publications
11
100
2
1
Order By: Relevance
“…One study has reported that sRAGE was elevated in patients with sepsis and was associated with patient outcome (23). Another study demonstrated that the sRAGE level was elevated during acute lung injury or acute respiratory distress syndrome, regardless of the presence or absence of severe sepsis (26). It has also been revealed that the level of serum sRAGE was elevated in breast cancer patients (27), and the elevated serum sRAGE levels were reported to be associated with an increased risk of cardiovascular disease in Japanese patients with type 2 diabetes (28).…”
Section: Discussionmentioning
confidence: 99%
“…One study has reported that sRAGE was elevated in patients with sepsis and was associated with patient outcome (23). Another study demonstrated that the sRAGE level was elevated during acute lung injury or acute respiratory distress syndrome, regardless of the presence or absence of severe sepsis (26). It has also been revealed that the level of serum sRAGE was elevated in breast cancer patients (27), and the elevated serum sRAGE levels were reported to be associated with an increased risk of cardiovascular disease in Japanese patients with type 2 diabetes (28).…”
Section: Discussionmentioning
confidence: 99%
“…Later studies found an association of sRAGE with severity (29) and outcome (30) in patients with ARDS. Other investigators (31) have reported higher levels of sRAGE in ARDS patients with or without sepsis when compared to patients that only had sepsis but not ARDS. These investigators also showed a correlation of RAGE with lung injury severity, but not with outcome (31).…”
Section: Receptor For Advanced Glycation End-products (Rage)mentioning
confidence: 97%
“…Other investigators (31) have reported higher levels of sRAGE in ARDS patients with or without sepsis when compared to patients that only had sepsis but not ARDS. These investigators also showed a correlation of RAGE with lung injury severity, but not with outcome (31). A recent meta-analysis suggested sRAGE as a biomarker strongly associated with diagnosis of ARDS in a high-risk population, but not associated with mortality (16).…”
Section: Receptor For Advanced Glycation End-products (Rage)mentioning
confidence: 97%
“…Further studies suggested that the activation of RAGE plays a role in various inflammatory and infectious diseases (4)(5)(6), acute respiratory distress syndrome (ARDS), and acute lung injury (ALI) (7,8). Soluble receptor for advanced glycation end products (sRAGE) consists of the extracellular domain but lacks the trans-membrane and cytoplasmic domains of RAGE in human plasma (9). sRAGE may have an inflammatory or homeostatic role to play in lung tissue (5,10), and is studied as an effective biomarker in ARDS (8,10), ALI (8,10), lung cancer (11) and chronic obstructive pulmonary disease (12).…”
Section: Introductionmentioning
confidence: 99%